Damage evolution and fracture characteristics of coal rock impacted by self‐excited pulse water jet under different stress loading conditions - Hongyu Ma; Wen Wan; Dongfang Xu; Pengtao Zhao; Jiaokun Wu; Yong Chen; Yao Wang (Energy Science & Engineering)
Abstract In this paper, based on smoothed‐particle hydrodynamics‐finite element method, numerical models of plunger squeezing water at a sinusoidal velocity were established to simulate self‐excited pulse water jet (SEPWJ). RHT constitutive model was adopted to describe the damage and failure of coal rock impacted by water jet. The morphological evolutions of broken pits and timeliness of rock‐breaking efficiency of SEPWJ and continuous water jet (CWJ) under the conditions with and without stress loadings were obtained and compared. The evolution laws of damage and stress inner coal rock induced by jet impact, and the failure mechanism were revealed. And the influences of different stress loading magnitudes on the fracture characteristics of coal rock were investigated. The results show that the morphologies of broken pits formed by self‐excited pulse jet undergo changes in a semi‐circular, U‐shaped, V‐shaped, and bullet shaped in sequence under the stress‐free loading condition. When applying one‐dimensional (1D) and 2D stress loadings, the shallow but wide broken pits with laminar main cracks along the stress loading direction and the inverted trapezoidal bowl broken pits are formed, respectively. With the increase of 1D stress, the depth and width of broken pits slightly decrease as a quadratic parabolic function and linearly increase, respectively. And the broken pit width and area both show an exponential slow decreasing trends with the increasing 2D stress. SEPWJ can induce higher stresses to cause the earlier occurrence of initial damage and the shorter duration of damage accumulation to coal rock than CWJ, which leads to a better rock‐breaking effect. The surface and deeper coal rock elements are broken mainly due to compressive shear stresses. The 2D stress loading delays the initial damage occurrence and prolongs the damage accumulation duration due to inhibitory effect of stress loading on jet impact.